2010
DOI: 10.1017/s0950268810002700
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial resistance ofEscherichia coliandEnterococcus faecalisin housed laying-hen flocks in Europe

Abstract: The aim of this study was to determine the potential association between housing type and multiple drug resistance (MDR) in Escherichia coli and Enterococcus faecalis isolates recovered from 283 laying-hen flocks. In each flock, a cloacal swab from four hens was collected and produced 1102 E. coli and 792 E. faecalis isolates. Broth microdilution was used to test susceptibility to antimicrobials. Country and housing type interacted differently with the MDR levels of both species. In the E. coli model, housing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
11
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 35 publications
2
11
0
Order By: Relevance
“…These properties are appropriate for a live vaccine candidate, since field usage of such a mutant would not spread virulence‐associated or drug resistance‐encoding genes to wild APEC. Emergence of drug resistance (4, 5, 8–12) and costs associated with administration of drugs have led to increased medical costs worldwide. Ozawa et al (11) reported APEC isolates in Japan have moderate‐ or high‐level resistance to many antimicrobials, including fluoroquinolones.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These properties are appropriate for a live vaccine candidate, since field usage of such a mutant would not spread virulence‐associated or drug resistance‐encoding genes to wild APEC. Emergence of drug resistance (4, 5, 8–12) and costs associated with administration of drugs have led to increased medical costs worldwide. Ozawa et al (11) reported APEC isolates in Japan have moderate‐ or high‐level resistance to many antimicrobials, including fluoroquinolones.…”
Section: Discussionmentioning
confidence: 99%
“…Colibacillosis results in significant economic losses to the poultry industry each year. Traditionally, antibiotic agents have been used to control APEC infections (3–7), but the emergence of drug‐resistant mutants (4, 5, 8–12) and the demand for chemical‐free feeding have led to increased interest in alternative methods of protecting flocks against APEC.…”
mentioning
confidence: 99%
“…The potential transmission of these bacteria to human beings and the contamination of the environment by manure or airborne emissions are critically judged ( van den Bogaard et al, 2001 ; Khanna et al, 2008 ). Furthermore, E. coli isolates from animals and other sources of animal husbandry act as indicator bacteria to monitor the occurrence and persistence of antimicrobial resistance in food animals ( van Hoorebeke et al, 2011 ). Dusts from farm animal houses seem to be potential reservoirs of E. coli ( Harry, 1964 ).…”
Section: Introductionmentioning
confidence: 99%
“…To reduce the time required for testing, different methods have been developed 8 including tests based on novel reagents, yet these tests are generally used to supplement rather than replace existing methods. The exception is the methodology based on PCR, which has progressively been replacing with biochemical and agglutination tests 14,30 . With poultry, control of infection depends largely on the identification of the infection in the early stages.…”
Section: Introductionmentioning
confidence: 99%